(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
This paper discussed the performance of a wineglass-shaped antenna fabricated on transparent (indium tin oxide on glass) and non-transparent (Rogers RT6006) substrates. Simulated and measured results of coefficient reflection, VSWR, and radiation patterns are compared and analyzed. Both antennas are well matched at the designed frequency with good reflection coefficient. The non-transparent antenna minimum coefficient reflection is -35.45 dB, and the transparent antenna reached the value of -19.71 dB. The non-transparent antenna has higher gain and exhibits symmetrical radiation. The study demonstrates the feasibility of both transparent and non-transparent wineglass antennas at 28 GHz, with the non-transparent offering higher gain and better impedance matching from a better conductivity compared to the transparent material used.